Study on the triaxial creep and acoustic emission characteristics of surrounding rock in high-stress caverns under different initial damage levels - Peng, Qingtao; Li, Kegang; Shi, Ji; Li, Mingliang; Qin, Qingci (Frontiers in Earth Science, 2025)
To investigate the creep behavior of deep hard rock under varying initial damage conditions, brittle dolomite specimens were subjected to different pre-peak strengths under a confining pressure of 30 MPa to induce distinct initial damage levels. Subsequently, creep and acoustic emission (AE) tests were conducted on these specimens under constant confining pressure and stepwise increasing axial pressure. The study focused on characterizing the temporal evolution of axial strain and the features of AE signals, including ring counts and energy, under different stress paths. Furthermore, scanning electron microscopy (SEM) was employed to elucidate the underlying mechanisms of creep failure. The results revealed that: (1) Under stepwise loading, the axial strain of dolomite specimens with varying initial damage levels exhibited a stepwise increase. It was observed that the axial strain at the same stress level increased with the damage level, leading to earlier specimen failure. (2) Acoustic emission demonstrated distinct time-dependent characteristics that closely correlated with the entire creep process. During the deceleration creep stage, AE signals were abundant and active; in the steady-state stage, the signals remained low and stable; whereas in the acceleration stage, the signals increased explosively and reached their maximum values. Moreover, specimens with greater initial damage displayed earlier peaks in both ring counts and cumulative energy, indicating an earlier failure. (3) The creep failure of dolomite under different damage levels was primarily attributed to the expansion of intergranular spacing and the fracture of mineral grains under high stress levels. These findings provide a reliable basis for the development of a nonlinear damage model for dolomite and offer novel insights into the triaxial creep mechanical properties of dolomite with varying initial damage levels under high stress conditions.